POTENSI PRODUKSI FRUKTOOLIGOSAKARIDA (FOS) MELALUI UJI TUMBUH KAPANG Aspergillus niger PADA BEBERAPA MEDIA BAHAN PANGAN ASAL SULAWESI UTARA (POTENCY FOR FRUCTOOLIGOSACCHARIDES PRODUCTION THROUGH GROWING TEST OF Aspergillus niger ON SOME TYPICAL FOODSTU - Mamuaja, Meiske N.; Berhimpon, Siegfried; Mamuaja, Christine F. (Jurnal Ilmu dan Teknologi Pangan, 2014)
The increasing of metabolic disease due to the over consumption throughout the world become a challenge for the development of functional food that rich in nutrition and also can provide health benefit for human consumption.  The objective of this research is to found the possibility of using some typical foodstuffs from North Sulawesi, i.e pisang goroho (Musa acuminate), sweet potato (Ipomeae batatas), palm sugar and coconut water, as a medium for Aspergillus niger growth in order to produce fructooligosaccharide (FOS), a functional food.  This research was done by laboratory experiment for the growing test of Aspergillus niger in 5 mediums with 4 replications.  Statistical analysis of the results shown that the Aspergillus niger tend to grow in 4 of 5 mediums which indicate the possibility of fructooligosaccharide production in those medium.  Further studies are needed in order to know the amount production of fructooligossaccharide based on its medium.